Young Voters and Budget Deficits - Ole Henning Nyhus; Bjarne Strøm (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper exploits a novel trial in Norwegian local elections in 2011 to provide empirical evidence on fiscal performance from lowering the minimum voting age from 18 to 16. Using a difference in differences research strategy, we find that this voting age change reduced the net operating surplus by around 600NOK ( exteuro60) per capita. This finding is consistent with micro evidence that young individuals have higher discount rates and are more likely to take risk than older ones, although other evidence is needed to confirm that interpretation. Further heterogeneity analysis demonstrates that increased deficits (reduced net operating surplus) due to the extension of the youth voting franchise mainly appear in governments with low party fragmentation and a large share of socialist politicians in the local council.
Keywords: C23; D72; H72; 330; local public finance; fiscal performance; minimum voting age